Microtubules in Microorganisms: How Tubulin Isotypes Contribute to Diverse Cytoskeletal Functions - Bera, Abesh; Gupta, Mohan L. (Frontiers in Cell and Developmental Biology, 2022)
The cellular functions of the microtubule (MT) cytoskeleton range from relatively simple to amazingly complex. Assembled from tubulin, a heterodimeric protein with alpha- and beta-tubulin subunits, microtubules are long, hollow cylindrical filaments with inherent polarity. They are intrinsically dynamic polymers that utilize GTP binding by tubulin, and subsequent hydrolysis, to drive spontaneous assembly and disassembly. Early studies indicated that cellular MTs are composed of multiple variants, or isotypes, of alpha- and beta-tubulins, and that these multi-isotype polymers are further diversified by a range of posttranslational modifications (PTMs) to tubulin. These findings support the multi-tubulin hypothesis whereby individual, or combinations of tubulin isotypes possess unique properties needed to support diverse MT structures and/or cellular processes. Beginning 40 years ago researchers have sought to address this hypothesis, and the role of tubulin isotypes, by exploiting experimentally accessible, genetically tractable and functionally conserved model systems. Among these systems, important insights have been gained from eukaryotic microbial models. In this review, we illustrate how using microorganisms yielded among the earliest evidence that tubulin isotypes harbor distinct properties, as well as recent insights as to how they facilitate specific cellular processes. Ongoing and future research in microorganisms will likely continue to reveal basic mechanisms for how tubulin isotypes facilitate MT functions, along with valuable perspectives on how they mediate the range of conserved and diverse processes observed across eukaryotic microbes.